Gereja Dalam Pusaran Konsumerisme Dan Kealpaan Dalam Pekabaran Injil - Fery Rondonuwu; Tjutjun Setiawan; Ferry Simanjuntak (Sekola Tinggi Teologi Sangkakala Jakarta, 2021)
Perubahan zaman yang begitu cepat telah membawa budaya baru dalam masyarakat yaitu budaya konsumerisme. Suatu budaya yang menjadikan masyarakat berperilaku konsumtif yang tidak berdasar kepada kegunaan tetapi kepada gaya hidup. Pasar yang cenderung ekstrim dalam mempromosikan produknya, menjadi masalah bagi masyarakat, termasuk orang percaya yang merupakan bagian dari gereja bisa terjerat dalam pusaran konsumerisme. apakah konsumerisme telah masuk dalam gereja sehingga gereja lalai terhadap penginjilan, misi, penanaman gereja baru. Dalam studi ini penulis menggunakan metode kualitatif dengan pendekatan studi pustaka, melalui buku-buku referensi dan jurnal-jurnal, serta ayat-ayat Alkitab yang berkaitan dengan rumusan masalah, kemudian mencari kesamaan yang memungkinkan bisa menjawab masalah penelitian ini. Dari penelitian ini didapati bahwa konsumerisme telah masuk dalam gereja, untuk itu gereja diingatkan agar waspada, kritis, bersikap tegas terhadap konsumerisme dan melakukan evaluasi yang objektif, sehingga gereja kembali menjalankan Amanat Agung tanpa terjebak budaya konsumerisme. AbstractThe changing times are so fast that it has produced a new culture in society, which is the culture of consumerism. A culture that makes people behave consumptively not based on utility but lifestyle. Market conditions that tends to be extreme in promoting their products are a problem for the community, also for believers, who are part of the church, who can get caught in the vortex of consumerism. It not only affects individuals, but also the church. The church spent most of their budget on providing luxurious and sophisticated infrastructure so that there is no budget left for evangelism, missions, and new church planting. This is a kind of another form of consumerism in the church. In this paper, the author uses a qualitative method with a literature study approach, through reference books and journals, as well as Bible verses related to the formulation of the problem, then finds for similarities that allow the author to answer this research problem. The conclusion of this study is that consumerism has entered the church, for that the church is reminded to be vigilant, critical, be firm towards consumerism and conduct an objective evaluation, so that the church returns to carrying out the Great Commission without being trapped in a consumerist culture. One of the best ways to get the church free from the trap of consumerism is to reimagine the purpose of the church's existence, which is to carry out the Great Commission and adjust the budget according to this top priority.